Analisis Kebutuhan Media Pembelajaran IPAS Berbasis Buku Cerita Bergambar Bermuatan Prinsip Pembelajaran Mendalam di Sekolah Dasar - I Gde Andika Yudha Pradana; I Made Ari Winangun; I Ketut Suparya (Jayapangus Press, 2026)
Learning Natural and Social Sciences (IPAS) in elementary schools requires deep and contextual conceptual understanding. However, classroom practices remain dominated by teacher-centered approaches and conventional learning media, which contribute to low student learning outcomes. This study aims to analyze the needs for developing IPAS learning media in the form of illustrated storybooks integrated with deep learning principles. The study employed a research and development approach focusing on the needs analysis stage and used a descriptive method combining qualitative and quantitative data. The research subjects were fourth-grade teachers and students from six elementary schools in Cluster 7, Tabanan District. Data were collected through classroom observations, teacher interviews, student questionnaires on learning media needs, and document analysis of student learning outcomes. The results show that IPAS instruction is still dominated by lecture-based methods with limited use of visual and contextual media. Quantitatively, only 32% of students achieved the Minimum Learning Achievement Criteria, with an average score of 61.7, particularly indicating difficulties in tasks requiring conceptual understanding and contextual application. Both teachers and students expressed a strong need for visually rich and contextual story-based learning media that are easy to use and relevant to students’ daily lives. These findings position needs analysis as a critical empirical foundation for developing IPAS learning media in the form of illustrated storybooks integrated with deep learning principles, an area that has received limited attention in previous studies. Therefore, the development of such media is considered a crucial pedagogical step to support more meaningful, reflective, and student-centered IPAS learning in elementary schools.